Is “Good Enough” Computing Good Enough? - Kugler, Logan (Communications of the ACM, 2015)
The article looks at the practice of approximate computing, in which the accuracy of a computing device's processing is reduced in order to reduce the amount of energy it consumes. According to the author, errors can be tolerated in programming applications such as video rendering, voice recognition, and web searching. Details on the role of hardware in energy-saving processes associated with approximate computing are presented. Other topics include hardware acceleration, computer performance, data partitioning, and the Rely programming language.